Media consumption of different cohorts: TV and Internet - M. M Nazarov; V. N Ivanov; E. A Kublitskaya (RUDN journal of Sociology, 2020)
The article considers the dynamics of the TV and Internet consumption of different cohorts under the dramatic changes in the Russian media landscape. In the last decade, the media environment has reached the mass scale in the use of the latest communication technologies based on the high-speed mobile Internet and its various apps. The results of the comparison of the studies of 2012 and 2017 indicate multidirectional trends: an increase in the average daily time of the Internet use in the middle-age and partly elder cohorts, and a moderate increase in the younger groups. The duration of TV viewing is a cyclic phenomenon determined by the stages of life cycle and socialization: the TV consumption of the same cohorts tends to decrease in a five-year interval. According to the theory of media substitution, the Internet is partly a functional alternative to TV for it allows the needs of the audience to be more fully satisfied and to develop on the basis of new technological opportunities. The article also considers features of the media consumption of the digital generation (millennials). This group is internally very different: it consists of several age and social-professional subgroups with serious differences in the average daily TV and Internet consumption. All these trends of the media consumption changed under the covid-19 crisis: changes in the mode of life and a fundamentally different information agenda determined an increase in the media use, primarily TV and the Internet. The long-term trend of the gradual decrease of the TV-audience changed: the average TV viewing increased in all cohorts. Under the crisis, the leading functions of the media - information and recreation - are more in demand than before.